THE EFFECTS OF FOREBRAIN MULTIPLE LESIONS ON THE PRESSOR-RESPONSE INDUCED BY BILATERAL CAROTID OCCLUSION IN CONSCIOUS RATS - Decastro, MTBB; Decastro, JCB; Menani, Jose Vanderlei [UNESP] (Elsevier B.V., 1993)
In the present study, the effects of electrolytic lesions of the anteroventral third ventricle (AV3V) region and of the medial forebrain bundle (MFB) on the pressor response induced by bilateral carotid occlusion (BCO) in conscious intact and aortic baroreceptor-denervated (AD) rats were investigated. In intact control rats, BCO during 60 s produced a pressor response that could be divided into an early response (ER = 50 +/- 3 mmHg) that reachs a peak during the first 20 s and a sustained late response (LR), smaller than ER (32 +/- 2 mmHg), observed during the last 30 s. In intact-innervated rats, AV3V lesion (2 days) reduced ER (22 +/- 3 mmHg) and LR (16 +/- 2 mmHg), whereas the bilateral MFB lesions (6 days) mainly reduced LR (9 +/- 1 mmHg). Rats with simultaneous lesion of both the AV3V region and the MFB showed additional reduction of the ER (15 +/- 3 mmHg), but not LR (11 +/- 1 mmHg) when compared to the effect of MFB lesions alone. Compared to the AV3V lesion alone, LR but not ER was reduced in rats with a double lesion. In sham-lesioned rats, AD induced a significant increase in the pressor response to BCO (ER = 75 +/- 4 mmHg and LR = 65 +/- 3 mmHg) when compared to intact controls. A similar reduction in ER and LR was observed in AD rats after AV3V (ER = 35 +/- 3 mmHg and LR = 40 +/- 2 mmHg) and MFB (ER = 49 +/- 6 mmHg and LR = 41 +/- 5 mmHg) lesions alone or combined (ER = 40 +/- 6 mmHg and LR = 35 +/- 7 mmHg). The results showed that simultaneous lesions of both the AV3V region and the MFB practically abolished the pressor response to BCO. They also suggested that aortic baroreceptor activity plays a significant role in the effects of AV3V and MFB lesions on the pressor response to BCO.
Keywords: CAROTID OCCLUSION; AV3V; HYPOTHALAMUS; BARORECEPTOR; CEREBRAL ISCHEMIA; CARDIOVASCULAR REFLEX